Understanding the Adjustment Issues in Digital Humanities Among Female Academics in Advanced Career - Gbenusola Akinwale; Victor Ojakorotu (Noyam Journals, 2024)
It is no news that the world is a global village, the trend and advancement in digital content are not limited to the Sciences, Technology, Engineering and Mathematics (STEM), but have extended to the humanities as well. Digital humanities are a new pathway to modern research in humanities. Pedagogy in traditional humanities has changed in the last few decades. Academics are now compelled to teach, research and offer their services with the latest innovations. There are numerous challenges with catching up with the glimpse of digital technology in service delivery in all areas of research in current times. Dealing with large data seems impossible and time-wasting with the traditional Pedagogy of humanities. Female academics in advanced careers are facing more challenges in learning and using digital tools in their day-to-day activities, hence several of them are perceived or seen as inefficient/stagnated in advancing their careers. This study identified the adjustment issues particularly faced by female advanced career academics. The study used a mixed method approach to select ten (n=10) female academics with a mean age of 60 who were purposively selected for the study from the University of Lagos, Nigeria. The participants agreed that adjusting to digital humanities has been challenging and they highlighted the present state of their abilities in using digitals as instructional materials. The study concluded that the challenges confronting female academics are numerous, hence why catching up with the digital humanities and other related issues is responsible for the stagnation and less research output among female academics. The study recommended that there should be continuous training programmes for female academics in Nigeria. This study contributes to the growing literature on empowering women in academia.